Memahami Perilaku Mengemudi Berisiko: Perspektif Faktor Demografi Pengendara Sepeda Motor - Ahmad Fauzi; I Made Suraharta; Sri Sarjana (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
The high level of involvement of motorcyclists in traffic accidents highlights the importance of understanding the psychological factors that influence risky driving behavior, particularly attitudes toward safety. This study aimed to examine the influence of attitudes on two dimensions of risky driving behavior—violations and errors—and to identify differences in the strength of these influences based on rider demographic characteristics. The study used a quantitative approach with a cross-sectional design on 206 motorcyclists in Tegal City, analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and Permutation Multi-Group Analysis. The results showed that attitudes significantly influenced both violations (β = 0.460; p < 0.001) and errors (β = 0.530; p < 0.001), with a stronger influence on errors. Cross-group analysis revealed that the mechanism of attitude influence was not uniform: the influence on errors was strongest among riders aged 18–25 years, while the influence on violations was greatest among riders aged >36 years. Educational level significantly moderated the relationship, with less educated drivers demonstrating higher attitudinal sensitivity across both dimensions of risky behavior. Furthermore, driver training was shown to attenuate the influence of attitudes toward violations. These findings confirm that the effectiveness of traffic safety interventions depends on driver segmentation, with an emphasis on shaping safety attitudes and self-regulation tailored to demographic characteristics.